2020
DOI: 10.3390/ijerph17030838
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gintonin-Enriched Fraction on Methylmercury-Induced Neurotoxicity and Organ Methylmercury Elimination

Abstract: Gintonin is a newly discovered ingredient of ginseng and plays an exogenous ligand for G protein-coupled lysophosphatidic acid receptors. We previously showed that gintonin exhibits diverse effects from neurotransmitter release to improvement of Alzheimer’s disease-related cognitive dysfunctions. However, previous studies did not show whether gintonin has protective effects against environmental heavy metal. We investigated the effects of gintonin-enriched fraction (GEF) on methylmercury (MeHg)-induced neuroto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Moreover, it was shown that gintonin regulates the expression of VEGF in astrocytes, which might provide protection against hypoxic injury [ 76 ]. It has been suggested that gintonin is able to protect mouse brain against methylmercury-induced neurotoxicity and learning processes [ 77 ]. One of the most common mechanisms, which has been extensively highlighted in a study of gintonin, is its antioxidant effects; a simple diagram is given here ( Figure 8 ).…”
Section: Effects Of Gintonin Against Different Models Of Neurodegmentioning
confidence: 99%
“…Moreover, it was shown that gintonin regulates the expression of VEGF in astrocytes, which might provide protection against hypoxic injury [ 76 ]. It has been suggested that gintonin is able to protect mouse brain against methylmercury-induced neurotoxicity and learning processes [ 77 ]. One of the most common mechanisms, which has been extensively highlighted in a study of gintonin, is its antioxidant effects; a simple diagram is given here ( Figure 8 ).…”
Section: Effects Of Gintonin Against Different Models Of Neurodegmentioning
confidence: 99%
“…These results are also consistent with another report that 1 μM MeHg induces oxidative stress and subsequent cell death in SH-SY5Y cells [ 22 ]. MeHg was previously shown to increase intracellular ROS [ 16 , 17 ], causing lipid peroxidation and leading to intracellular oxidative stress [ 30 ]. Together, these findings indicate that oxidative stress is one of the main mechanisms of MeHg-induced CNS damage [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are several mechanisms of MeHg-induced injury, in which ROS are an important factor [ 14 ]. MeHg can increase intracellular ROS [ 15 , 16 ] and cause lipid peroxidation, which leads to oxidative stress in cells [ 17 ] and exerts toxic effects [ 18 ]. Therefore, the activation of antioxidant mechanisms prevents MeHg poisoning [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study found PCN to be affecting the locomotor activity of the subjects as well as their immobility behavior. PCN has also been used to induced ROS in human neural progenitor cells (hNPCs), mediated its oxidative stress levels using gintonin-enriched fraction [ 32 ].…”
Section: Introductionmentioning
confidence: 99%